Growth of SnO2 Nanoflowers on N-doped Carbon Nanofibers as Anode for Li- and Na-ion Batteries - Liang, Jiaojiao; Yuan, Chaochun; Li, Huanhuan; Fan, Kai; Wei, Zengxi; Sun, Hanqi; Ma, Jianmin (Nano-Micro Letters, 2017)
It is urgent to solve the problems of the dramatic volume expansion and pulverization of SnO2 anodes during cycling process in battery systems. To address this issue, we design a hybrid structure of N-doped carbon fibers@SnO2 nanoflowers (NC@SnO2) to overcome it in this work. The hybrid NC@SnO2 is synthesized through the hydrothermal growth of SnO2 nanoflowers on the surface of N-doped carbon fibers obtained by electrospinning. The NC is introduced not only to provide a support framework in guiding the growth of the SnO2 nanoflowers and prevent the flower-like structures from agglomeration, but also serve as a conductive network to accelerate electronic transmission along one-dimensional structure effectively. When the hybrid NC@SnO2 was served as anode, it exhibits a high discharge capacity of 750 mAh g−1 at 1 A g−1 after 100 cycles in Li-ion battery and 270 mAh g−1 at 100 mA g−1 for 100 cycles in Na-ion battery, respectively. Highlights: 1 A hybrid structure of SnO2 nanoflowers grown on N-doped carbon nanofibers (NC@SnO2) was successfully constructed. 2 N-doped carbon nanofiber accelerates the migration of Li+/Na+ ions and guides the growth of the SnO2 nanoflowers. 3 NC@SnO2 electrode reveals excellent energy storage performance for Li- and Na-ion batteries.